A point-of-use lateral flow aptasensor for naked-eye detection of aflatoxin B1 - Vijitvarasan P. (2023)
Aflatoxin B1 (AFB1) contamination in food is not only a serious health threat to humans, but also a considerable economic burden worldwide. Rapid and accurate detection of AFB1 during production, processing, transportation and storage is therefore a prerequisite to prevent spreading of AFB1. Here, we developed a simple and easy-to-use lateral flow aptasensor (LFA) to visually detect AFB1 using AFB1 aptamer. Polystyrene dyed particles were used as a signal reporter to enable colorimetric readout by naked eyes, in which the signal is directly proportional to the concentration of AFB1. Both aptamer specificity and target induced strand release approach enable a single-step AFB1 detection. The whole assay took 35 min to complete, starting from sample/dye complex incubation to color acquisition. Under the optimized condition, this sensing platform could detect AFB1 as low as 4.56 ng mL−1 with two distinct linear ranges of 0–0.05 μg mL−1 and 0.05–1 μg mL−1. LFA validation with 4 spiked samples (peanut, corn, rice and chili powder) showed satisfying AFB1 recovery within the range of 90.83–110.21%. Our LFA platform could potentially be applied to the on-site, naked-eye, and instrument-free detection of AFB1 or other substances with available aptamers.